The Incidence of Surgical Site Infection in Acute Non Perforated Appendicitis - Bhattarai, Suraj Raj; Tamrakar, Kishor Kumar (Journal of Chitwan Medical College, 2019)
Background: Appendectomy is the most commonly performed emergency  surgical procedure and has significant morbidity of surgical site infection (SSIs). Regarding this, there are conflicting reports and dilemma on use of optimal duration of antibiotics. The aim of this study was to evaluate the incidence of SSIs after three doses of perioperative prophylactic antibiotics (single dose before surgery and two doses postoperatively) after appendectomy in acute non- perforated appendicitis (NPA).Methods: This cross sectional study was conducted in the department of General surgery, Chitwan Medical College Teaching Hospital, from May 2018 to April 2019. All the cases received single dose of antibiotics (ceftriaxone and metronidazole) during the induction of anesthesia and two doses of the same antibiotics postoperatively within 24 hours. SSIs was assessed on 2nd and followed up till 7th postoperative day. The data collected was analyzed using SPSS version 16.Results: In the study of 100 patients, who received perioperative three doses of antibiotics, the overall frequency of SSIs on 2nd and 3rd post-operative day were 2% (p=.840) and 6% (p=.539) respectively, which was statistically not significant. In follow up after 3rd postoperative day, there was no evidence of SSIs. Statistically there was no significant difference in the incidence and grade of SSIs between age group, sex and duration of operation.Conclusions: A combined three doses of perioperative antibiotics was adequate for SSIs prevention in patients of any age group and sex with acute NPA after appendectomy in usual operative time.